Pengaruh Kualitas Pelayanan, Iklan, Persepsi Harga, Terhadap Kepuasan Pelanggan (Studi Pada Pengguna Gojek Di Kota Metro) - Idris, Muhammad Fahmi; Ratmono, Ratmono (Universitas Muhammadiyah Metro, 2023)
This study aims to determine the effect of service quality, advertising, price perception on customer satisfaction of gojek users in the city of Metro. This type of research is a quantitative study with an unknown population. Based on calculations using the Lemeshow formula, 96 samples were used that matched the predetermined criteria. The data used is secondary data distribution of questionnaires in the form of a list of questions with several alternative answers for respondents using a Likert scale. The statistical test used to test the hypothesis was multiple linear regression analysis and was tested using the statistical packages for the social science (SPSS) version 25 program. Based on the results of statistical tests, partial research shows that service quality has a positive and significant effect on customer satisfaction, advertising has a positive and significant effect on customer satisfaction, price perception has a positive and significant effect on customer satisfaction. Simultaneous research shows that service quality, advertising, price perception together affect customer satisfaction.